Implementation of lean manufacturing to increase the productivity of a peruvian textile SME - Ramos Tenorio, Sebastian Dario (2025)
Textile MSEs in Peru play an important role in business fabrics. However, small and medium-sized companies are facing different problems. Since they do not have the same purchasing power as large companies, it is difficult for them to implement advanced technologies or expensive machines that help reduce waste and improve production times, which leads to a decrease in productivity. The research has a mixed approach and a sequential design with a qualitative priority. It consists of two phases: in the first phase, qualitative tools will be applied to know and describe 100% of the problem to be addressed, and in the second phase, quantitative tools will be applied. The first tool to be used will be the Value Stream Map, which is used to know the current situation of the company and the future situation after implementation. It will be used to diagnose the company's problems and to model the solution. The second methodology to be implemented was the 5S, which follows a five-step process aimed at the correct division of resources, creation of culture and formation of discipline. The main objective of the research was to increase the productivity of the MSE, this was fulfilled by the application of the VSM and 5S tools, and the proposed improvements, reducing cycle times by 28.47% and shrinkage percentages by 18.43%